Transformational Leadership in The Hotel Industry: A New Look at The Service-Profit-Chain Concept - Teguh, Evelyn Devina; Devie, Devie; Wijaya, Serli (Petra International Journal of Business Studies, 2020)
Employee engagement is essential to the Service-Profit-Chain concept as the factor to produce high quality service that would meet or exceed customer expectations. However, despite its suggested advantages, limited knowledge is known about what causes employee engagement. This study attempts to understand the Service-Profit-Chain concept more comprehensively, by encompassing transformational leadership as the preceding factor to employee engagement. It aimed to examine the role of transformational leadership in shaping employee engagement and service quality which lead to financial performance. The sample groups taken were among the star-rated hotels located in Surabaya, Indonesia. Each hotel was represented by three groups namely: hotel managers, staff, and hotel customers. The Partial Least Square-SEM method was applied to evaluate the hypothesized model. The results revealed that the effect of transformational leadership on financial performance is mediated by employee engagement. However, service quality cannot mediate the effect of transformational leadership on financial performance. It is interesting to note that Service-Profit-Chain has some limitations in practice, depending on the organization’s strategy. This study is among a few attempts to contribute to a better understanding of the Service-Profit-Chain concept application, with transformational leadership as the factor preceding employee engagement specifically in the hotel industry. It founds that the application of Service-Profit-Chain concept in the hotels have some constraints related to the business strategy that hotels select to penetrate the market.